Trade in value added: Concepts, estimation and analysis - Marko Javorsek; Ignacio Camacho (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2015)
This working paper introduces the concept of Trade in Value Added (TiVA) and presents an initial analysis of TiVA for selected regional ESCAP economies. The paper introduces Global Value Chains (GVCs) and issues for the measurement of trade statistics due to proliferation of GVCs. It further presents the TiVA estimation methodology, as defined in the literature, and provides an overview of the data requirements for estimation. The paper reviews current initiatives on regional / international input-output tables (IOTs) and TiVA analysis, and availability of data in the Asia-Pacific region. The paper concludes with a TiVA analysis of selected regional ESCAP economies that are available in the current data sources. The paper has been prepared under the Regional Programme on Economic Statistics (PRES) and we hope it will support the efforts of statistical offices in the region to improve related statistics.
Keywords: C67; D57; F13; F14; F15; F23; O19; O24; 330; international trade statistics; trade in value added; global value chains; Asia and the Pacific; input-output; supply-use